PENGEMBANGAN MEDIA PEMBELAJARAN PRAKTIKUM VIRTUAL BERBASIS ANDROID UNTUK MENINGKATKAN BERPIKIR KREATIF SISWA - Yeni Suryaningsih; Aden Arif Gaffar; Muhamad Kurnia Sugandi (BIO EDUCATIO : (The Journal of Science and Biology Education), 2020)
ABSTRACT This study aims to determine the feasibility and interest of the virtual application learning media based on android applications on the concept of invertebrate animal material. This research is a research and development (R&D) that adopts the development model of Thiagrajan, S., et al. Using non-test data collection techniques in the form of expert / media expert questionnaire, material expert, and linguist expert and student response questionnaire. The results of the appraisal of androis-based virtual practicum learning media by experts / media experts were 71.7% with feasible criteria, the assessment of material experts was 91.5% with very decent criteria, 89.5% was assessed by linguists as very feasible criteria. Student response results by 77% in the interesting category. Based on the results of this study that the development of an Android-based virtual practicum learning media on the concept of invertebrate animals can be used as an alternative learning biology, especially preformance practicum activities, as well as increasing students' creative thinking.Keywords: virtual practicum, learning media, creative thinking, invertebrate animals.